Building Climate Resilient Agriculture in Caribbean Countries: Suriname - Hayman, Alicia A (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
Agriculture is a significant sector in Suriname, employing 17% of the population, but faces challenges such as low productivity, inadequate technology, and limited irrigation. The country has prioritized climate resilient agriculture (CRA) actions in its NDCs but faces barriers to implementation, including limited data availability, financial resource constraints, and land tenure insecurity. Suriname has implemented several CRA programs with government and donor support and can further enhance CRA transition and climate ambition in its NDCs by evaluating mitigation actions in rice cultivation, livestock management, and nitrogen inputs while also implementing adaptation actions beyond the farmgate.